Microstructural Characteristics and Mechanical Properties of Nanostructured and Conventional TiAlN and AlCrN Coatings on ASTM-SA210 Grade A-1 Boiler Steel. (18th August 2013) - Chawla, Vikas
Abstract : Nanostructured and conventional TiAlN and AlCrN coatings were deposited on ASTM-SA210 Grade A-1 boiler steel. The present work has been focused to characterize the conventional thick (by plasma spraying and gas nitrided) and nanostructured thin (by physical vapor deposition process) TiAlN and AlCrN coatings developed on ASTM-SA210 Grade A-1 boiler steel. The surface morphology of the coated samples was studied using FE-SEM with EDAX attachment, XRD analysis, AFM analysis, and the X-ray mapping analysis. The presence of metal nitride phases as identified by XRD analysis indicates that the desired coatings were successfully developed. The bond strength, surface roughness, and microhardness of the gas nitrided plasma sprayed conventional coatings were measured. A good adhesion of the conventional thick TiAlN and AlCrN coatings was evident from bond test results.